1976
DOI: 10.1042/bj1580191
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism in perfused skeletal muscle. Effects of starvation, diabetes, fatty acids, acetoacetate, insulin and exercise on glucose uptake and disposition

Abstract: 1. The regulation of glucose uptake and disposition in skeletal muscle was studied in the isolated perfused rat hindquarter. 2. Insulin and exercise, induced by sciatic-nerve stimulation, enhanced glucose uptake about tenfold in fed and starved rats, but were without effect in rats with diabetic ketoacidosis. 3. At rest, the oxidation of lactate (0.44,umol/ mi per 30g ofmuscle in fed-rats) was decreased by 75% in both starved and diabetic rats, whereas the release of alanine and lactate (0.41 and 1.35,umol/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
6
1

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(102 citation statements)
references
References 32 publications
(49 reference statements)
7
88
6
1
Order By: Relevance
“…One possible factor is the greater enzymic capacity of heart to oxidize lipids (Winder et al, 1974;Holloszy et al, 1973). Another is that the heart is a continuously contracting muscle with a high rate of glycolysis Randle, 1966) compared with perfused skeletal muscle Goodman et al, 1974;Berger et al, 1976) and presumably non-exercising muscle in vivo Wahren et al, 1971). In keeping with this notion, the glucose-fatty acid cycle has been demonstrated in brain , mammary tissue (Hawkins & Williamson, 1972;Williamson et al, 1974;Robinson & Williamson, 1977) and submaxillary glands (Thompson & Williamson, 1975), all of which have high rates of glycolysis and glucose oxidation.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…One possible factor is the greater enzymic capacity of heart to oxidize lipids (Winder et al, 1974;Holloszy et al, 1973). Another is that the heart is a continuously contracting muscle with a high rate of glycolysis Randle, 1966) compared with perfused skeletal muscle Goodman et al, 1974;Berger et al, 1976) and presumably non-exercising muscle in vivo Wahren et al, 1971). In keeping with this notion, the glucose-fatty acid cycle has been demonstrated in brain , mammary tissue (Hawkins & Williamson, 1972;Williamson et al, 1974;Robinson & Williamson, 1977) and submaxillary glands (Thompson & Williamson, 1975), all of which have high rates of glycolysis and glucose oxidation.…”
mentioning
confidence: 62%
“…Initial studies suggested that lipid fuels do not inhibit glucose utilization in incubated or perfused muscle (Beatty & Bocek, 1971;Jefferson et al, 1972;Goodman et al, 1974;Reimer et al, 1975;Berger et al, 1976), with the possible exception of diaphragm (reviewed by Ruderman et al, 1969), but that they inhibit glucose oxidation at the pyruvate dehydrogenase step (Berger et al, 1976;Hagg et al, 1976). More recently, inhibition of glucose utilization and glycolysis by fatty acids and ketone bodies has been demonstrated in rat soleus muscles incubated in vitro (Maizels et al, 1977;Pearce & Connett, 1980); however, contradictory findings have been reported in the isolated perfused, well-oxygenated, rat hindquarter Ruderman et al, 1980;Richter et al, 1982b).…”
Section: Introductionmentioning
confidence: 99%
“…Less clear is whether fatty acids and ketone bodies inhibit glucose uptake-and glycolysis during severe exhaustive exercise. In studies with the perfused rat hindquarter, Berger et al (1976) noted that acetoacetate inhibited glucose oxidation during isometric exercise induced by bilateral sciaticnerve stimulation at a rate of 5 per s. On the other hand, neither glucose uptake nor glycolysis was decreased, although tissue citrate was moderately increased. Whether inhibition ofglycolysis was missed because of a predominance of white muscle in the exercising portion of the hindquarter or because of other metabolic alterations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is general agreement that they displace glucose as a fuel in voluntary skeletal muscle by inhibiting pyruvate dehydrogenase (see Berger et al, 1976); however, it is not clear whether they also inhibit glucose uptake and glycolysis (reviewed by Ruderman et al, 1969Ruderman et al, , 1977see Berger et al, 1976). The present study suggests that this, in part, may be related to the heterogeneity of muscle fibres in voluntary muscle.…”
Section: Discussionmentioning
confidence: 99%
“…post-receptor defects) also contributed to insulin resistance [% 9, 10]. In insulinresistant muscles, several such post-receptor defects have been described [4,7,[10][11][12][13][14]. In isolated soleus muscles of the genetically obese Zucker (fa/fa) rat the following post-receptor abnormalities have been shown: (a) increased utilization of endogenous fatty acids inhibitory to glycolysis [7]; (b) decreased uptake of the D-glucose analogue, 2-deoxy-D-glucose (2-DG) [4,7,12].…”
mentioning
confidence: 99%